Neurological issues during COVID-19: An overview. (18th January 2021) - Nath, Avindra; Smith, Bryan
Highlights: The neurological manifestations of COVID-19 are the most disabling long-term complications. Will nearly 70 million people infected word-wide the the neuro-COVID has major socio-economic consequences. Abstract: COVID-19 has shaken the core of the medical health system. The wide spread death and destruction of patients and health care workers in unprecedented in the modern era. While the pulmonary complications have received the most attention, it is the neurological manifestations that are disabling, persistent and common in patients infected with SARS-CoV-2. The entire neuro-axis can be involved resulting in a wide variety of manifestations. While the pathophysiology is not well understood, many of the clinical manifestations seem to be immune mediated. The socio-economic consequences of these complications are dire. These unprecedented times also calls for unprecedented action. Novel clinical trial designs need to be considered so that multiple agents can be studied. In the context of these clinical trials, disease pathophysiology and standardized batteries and biological markers for patient assessment need to be developed.